Espressioni Letterali

  • Materia: Espressioni Letterali
  • Visto: 3403
  • Data: 30/12/2008
  • Di: Redazione StudentVille.it

$[(-3/2a^2b)^5:(-3/2a^2b)^3-(3/2a^2b)^2(-4ab^3):(-2ab^3)]^2:(-1/2ab^2)^2+...$

esercizio svolto o teoria

A cura di: Francesco Speciale

Svolgimento:
$[(-3/2a^2b)^5:(-3/2a^2b)^3-(3/2a^2b)^2(-4ab^3):(-2ab^3)]^2:(-1/2ab^2)^2+(3/2ab)^3:(3/2ab)^3-[-(2/5ab^2)]^0=$
$=[(-3/2a^2b)^2-(9a^4b^2)(-4ab^3):(-2ab^3)]^2:(1/4a^2b^4)+1-1=$
$=[9/4a^4b^2-(-9a^5b^5):(-2ab^3)]^2:(1/4a^2b^4)=$
$=[9/4a^4b^2-9/2a^4b^2]^2:(1/4a^2b^4)=$
$=[(9-18)/4a^4b^2]:(1/4a^2b^4)=$
$=((81)/(16)a^8b^4):(1/4a^2b^4)=(81)/4a^6$.